THE LINGUISTIC POWER OF PERSONAL DRIVE IN THE GREATEST SHOWMAN - OMAR RABANI, SATYA (LANGUAGE HORIZON, 2019)
Politeness has become quickly to understand that can make things worse by wrong responding to the interlocutors. It has the strategy to show the power and treat the interlocutors. Besides, a movie that raised politeness entitled The Greatest Showman won a Golden Globes award for best original, which can have to categorize as something new. Thus, the researcher chose politeness strategies as a topic because of movie drama rarely thoughts about politeness.The aim of this research uses to find out what are the types of politeness strategies that constructed by the personal drive to motivate others and what are the factors that trigger the personal drive-in using politeness strategies to encourage others. This research used a qualitative approach to answer the research questions. The qualitative approach was chosen as the methodology to analyze the data findings because it is the most appropriate method to answer the research questions of the study. This research uses the politeness strategy leading the factor of language and power as the data which are spoken by the personal drive in The Greatest Showman movie. The study shows that four types of politeness strategies Brown and Levinson (1987) constructed by the personal drive to motivate the others, it also shows that factors of language and power Fairclough (1989) trigger politeness strategies due.